Households' food consumption behavior in Argentina: a quadratic demand system with demographic effects - Echeverría, Lucía (2015)
The objective of this paper is to analyze household's food consumption behavior in Argentina by comparing two cross sectional estimations system (QES). We employ data from the National Expenditure Survey at household level (2004-05 and 2012 demographical variables in order to examine changes across different household types. We estimate quality adjusted prices and we account for any selectivity bias in our data. In addition, we propose an exercise which consists on calculating equivalence scales from estimated expenditures for each household type. Results allow us to analyze an particular, changes in food consumption are led by changes in relative prices; inflation process unequally affects consumption of different food categories, implying that households' budget is being reallocated.